The Research Mapping the Effects of Project Based Learning on Students’ Digital Literacy: A Bibliometric Analysis - Farisi Engrini; Asrizal; Fatni Mufit; Fuja Novitra (Jurnal Penelitian Pendidikan IPA, 2026)
The integration of technology with project-based learning (PjBL) has become a key approach to fostering 21st-century skills, particularly digital literacy. However, research exploring the relationship between PjBL and digital literacy remains fragmented and lacks comprehensive mapping. This study aims to analyze research trends and thematic evolution related to PjBL and students’ digital literacy using a bibliometric approach. A total of 184 articles indexed in Scopus from 2015 to 2025 were analyzed using VOSviewer, including performance analysis, thematic mapping, and keyword co-occurrence. The results show a steady increase in publications, with a significant rise after 2020. The analysis identifies major research clusters focusing on digital literacy, immersive learning, instructional innovation, and interdisciplinary approaches. Furthermore, the findings suggest that PjBL is widely associated with enhancing student engagement, problem-solving skills, and broader 21st-century competencies. This study highlights emerging research directions, including the need for more robust pedagogical frameworks and increased cross-disciplinary collaboration. In conclusion, the integration of PjBL and digital literacy demonstrates strong potential to support more interactive and meaningful science learning aligned with digital era demands. Future research should focus on developing more adaptive and technology-integrated PjBL strategies.